Self-Stigma and Low Mental Health Literacy as Predictors of Help-Seeking Avoidance - Abdulhussein, Omar; El Amrani, Youssef; El-Sayed, Mona (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: This study aimed to investigate the predictive roles of self-stigma and mental health literacy in help-seeking avoidance among Moroccan adults. Methods and Materials: A correlational descriptive design was employed with a sample of 390 participants selected through random sampling based on the Krejcie and Morgan table. Data were collected using standardized tools: the Self-Stigma of Seeking Help Scale (SSOSH), the Mental Health Literacy Scale (MHLS), and the Attitudes Toward Seeking Professional Psychological Help Scale – Short Form (ATSPPH-SF). Descriptive statistics, Pearson correlation, and multiple linear regression analyses were conducted using SPSS-27 to explore relationships among the variables and assess the predictive power of the independent variables on help-seeking avoidance. Findings: Pearson correlation results indicated that help-seeking avoidance was significantly and positively correlated with self-stigma (r = .61, p < .001) and negatively correlated with mental health literacy (r = –.54, p < .001). The regression model was significant, F(2, 387) = 184.23, p < .001, with an R² of .49, indicating that 49% of the variance in help-seeking avoidance was explained by the predictors. Self-stigma significantly predicted help-seeking avoidance (B = 0.46, β = .49, p < .001), as did mental health literacy (B = –0.21, β = –.37, p < .001), with self-stigma having a stronger standardized effect. Conclusion: The results demonstrate that both high self-stigma and low mental health literacy are significant and independent predictors of help-seeking avoidance. Interventions aiming to increase mental health service utilization should address both cognitive knowledge gaps and internalized stigma. This dual approach may enhance openness to professional help, especially in sociocultural contexts where mental illness is stigmatized.